Zonas de manejo do teor de fósforo (P) e resposta da soja inoculada com solubilizador de fosfato - Guesser, Vagner Portes (2022)
Phosphorus (P) acts on the energy metabolism of plants and in most Brazilian soils its availability is low, and phosphate solubilizing microorganisms (MSP) are promising in the availability of P to plants, through the availability of insoluble phosphates. Also, the spatial variability of P can be estimated through precision agriculture and generate management zones for its availability. The work was carried out in the municipality of Dom Pedrito-RS, in an experimental area of 5.7 ha-¹ . The determination of the spatial variability of the P content in the soil was measured in a regular sampling grid with 40 points, from the layer 0 to 20 cm. The detection of spatial variability, geostatistical modeling, preparation of the thematic map of P content and generation of P management zones were performed using the QGIS software version 3.16, using the Smart Map plugin. The cultivar used was BMX Zeus Ipro with 18 seeds m-¹ , spaced 50 cm-¹ . The phosphorus solubilizer contained strains B119 (Bacillus megaterium) and B2084 (Bacillus subtilis) with 4x109 viable cells per ml of product, applied via directed jet in the sowing furrow at a dose of 200 ml-¹ of commercial product ha-¹ and flow of 20 liters ha-¹ . The soluble mineral source was applied to the sowing line at a dose of 80 kg ha-¹ of diphosphate pentoxide (P2O5). The experimental design was randomized blocks in a factorial scheme 2 (management zones) x 3 (sources of availability) and 4 replications. The P content in the grain (%), in the leaves (g kg-¹ dry matter) and in the soil (mg dm-¹ ), the weight of a thousand grains (g-¹ ) and the productivity (kg ha-¹ ). The thousand-grain mass increased by 5.84% with the solubilizer and 4.79% with the mineral P source. The P content in the grain was 5.55% higher with the mineral source, compared to the control, not differing from the levels observed for the solubilizer. The supply of P via mineral source resulted in higher P content in the soil after the soybean harvest. Productivity was higher with the mineral source and solubilizer, compared to the control. Management zones with higher P availability showed productivity 9.44% above the ZM with lower availability. The P content in the grains was higher in ZM with lower P availability. Yield is responsive to the addition of P in areas of lower availability, with an increase of 8.51% via solubilizer and 11.57% via mineral source, compared to the nonaddition of the nutrient. The delimitation of ZM, based on the availability of P in the soil, indicated a reduction in the cost of supplying P, either via mineral source or solubilizer. The P solubilizer was able to supply the soybean demand and can replace the mineral source when the P contents in the soil are above the lower limit of the average interpretation class.